Mummers' plays revisited - Harrop, Peter (Professor of Drama), author.
1 online resource.
Keywords: Peter Harrop offers a reappraisal of mummers' plays, which have long been regarded as a form of 'folk' or 'traditional' drama, somehow separate from the mainstream of British theatre. This fresh view of folk and tradition explores how mummers' plays emerged in an 18th century theatrical environment of popular spouting clubs and private theatricals, yet quickly transformed into 'traditionary' drama with echoes of an ancient past. Harrop suggests that by the late 19th century the plays had been appropriated by antiquarians and folklorists, leaving mummer's plays as a strangely separate and categorised form. This book considers how that happened, and the ways in which these late 19th century ideas were absorbed into the mummers' plays, providing a new lease of life for them in the 20th and 21st centuries. Ideal for anyone with a specialised interest in this unique form, Mummers' Plays Revisited spans recent work in theatre history, performance studies and folklore to offer a comprehensive and engaging study.